Bathing trunk naevus: a case report with dermoscopic findings in a brown child - Megha Shankar; Sambasiviah Chidambara Murthy (Wolters Kluwer Medknow Publications, 2021)
Giant congenital melanocytic naevus is a naevus measuring more than 20 cm in adulthood. Its incidence is 1:20,000 and is more common in girls. Bathing trunk naevus, a specific form of giant congenital melanocytic naevus is even rarer with incidence of 1:500,000. Giant congenital melanocytic naevus usually presents as a brown lesion, with flat or mamillated surface, well-defined borders and hypertrichosis. Dermoscopic examination of melanocytic naevi shows brown-blackish background, globules, reticular network and vascular structures. Although giant congenital melanocytic naevus is often diagnosed clinically, dermoscopy aids in detecting early changes of complications such as malignant melanoma. We report a case of bathing trunk naevus with multiple satellite lesions in a brown child with dermoscopic findings.